2020
DOI: 10.1186/s12886-020-01373-5
|View full text |Cite
|
Sign up to set email alerts
|

Phacoemulsification in patients with uveitis: long-term outcomes

Abstract: Background: To assess the long-term outcomes of phacoemulsification and intraocular lens (IOL) implantation in eyes with uveitis. Methods: One hundred and five eyes of 81 patients, who underwent phacoemulsification and IOL implantation between January 2009 and July 2016, were included in this study. The demographic data, preoperative clinical findings, postoperative outcomes, and intraoperative and postoperative complications were recorded. All collected data and risk factors with regard to visual prognosis we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 40 publications
5
16
2
1
Order By: Relevance
“…In contrast, there is a significant literature showing post-cataract surgery complications in patients with uveitis, particularly if inflammation is not controlled prior to surgery. The complications of cataract surgery in patients with uveitis include PCO, glaucoma, macular edema, and retinal detachments [173,[203][204][205], evidence that many regions of the eye are impacted by ocular inflammation after cataract surgery. Together with the discovery that immune surveillance of the lens is induced when the cornea is wounded [163] and the surveillance of the cornea and retina by immune cells in induced in response to lens degeneration [164], these findings demonstrate that immune responses across the eye are highly interactive.…”
Section: The Impact Of Uveitis On Cataract Surgery Outcomesmentioning
confidence: 99%
“…In contrast, there is a significant literature showing post-cataract surgery complications in patients with uveitis, particularly if inflammation is not controlled prior to surgery. The complications of cataract surgery in patients with uveitis include PCO, glaucoma, macular edema, and retinal detachments [173,[203][204][205], evidence that many regions of the eye are impacted by ocular inflammation after cataract surgery. Together with the discovery that immune surveillance of the lens is induced when the cornea is wounded [163] and the surveillance of the cornea and retina by immune cells in induced in response to lens degeneration [164], these findings demonstrate that immune responses across the eye are highly interactive.…”
Section: The Impact Of Uveitis On Cataract Surgery Outcomesmentioning
confidence: 99%
“…However, Abbouda et al found that eyes with what they defined as having more than one ''postoperative relapse year'' had a trend towards worse visual acuity outcomes, though this difference was not statistically significant [14]. Ozates et al found uveitis relapse rates actually decreased overall postoperatively in a group of 105 eyes, though not commenting or differentiating visual acuity outcomes from those that did recur early versus those that did not [15]. In addition, Reddy et al showed that among eyes without prior uveitis, 3-month postoperative visual acuity outcomes were no different in eyes that had persistent anterior uveitis after surgery versus those that did not [3].…”
Section: Discussionmentioning
confidence: 99%
“…Cataract surgery should therefore only be performed after the suppression of inflammation for at least 3 months, and these results are consistent with previous reports. 8,[18][19][20] For vitrectomy, about 50% of patients had vitreous opacity, and malignant lymphoma and sarcoidosis seemed to be the underlying diseases, although vitrectomy for inflammatory eyes with vitreous opacity of unknown etiology has been reported. 21 In the present study, the mean VA was significantly improved after vitrectomy, but 14.2% of patients required the reoperation, which seems a high incidence.…”
Section: Discussionmentioning
confidence: 99%